Study on the Influence of Grounding Resistance on Cable Fault Overvoltage - Baotong Song; Sihan Wang; Changyuan Xiang; Xiaoyue Chen; Ju Tang (Energies)
The cable grounding connecting method and grounding resistance have a significant influence on the cable fault overvoltage. This paper considers a 500 kV long cable project in Beijing as the research object; a model was implemented in ATP-EMTP, and simulation results show how grounding resistance and its connection method influence the cable fault overvoltage. When the grounding resistances are all set to the same value along the cable, as the grounding resistance increases, the frequency of overvoltage at the cable fault point also increases. When all grounding resistances along the cable are set to same value, if a connection method considering conduction impedance is adopted, the fault point frequency overvoltage also increases. If the grounding resistance at both ends of the cable are connected to the substation, the sequence impedance of the cable will decrease, resulting in a reduction in the fault point overvoltage. Additionally, this paper analyzes the influence of grounding material on the cable line sequence impedance. When the grounding resistance value is set to 5 Ω according to the national standard, the cable line fault overvoltage under single-phase grounding fault with load reduction is simulated and analyzed, and it is found that connecting the grounding devices at both ends of the cable to the substation can effectively suppress the overvoltage along the cable.